2015
DOI: 10.3109/1547691x.2015.1045636
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3-dimensional culture conditions (collagen-chitosan nano-scaffolds) on maturation of dendritic cells and their capacity to interact with T-lymphocytes

Abstract: In the body, there is a natural three-dimensional (3D) microenvironment in which immune cells, including dendritic cells (DC), play their functions. This study evaluated the impact of using collagen-chitosan 3D nano-scaffolds in comparisons to routine 2D culture plates on DC phenotype and functions. Bone marrow-derived DC were cultured on scaffolds and plates and then stimulated with lipopolysaccharide (LPS) or chitosan-based nanoparticles (NP) for 24 h. Thereafter, DC viability, expression of maturation marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Indeed, cell culture in a threedimensional spatial arrangement has been reported to affect a range of cellular functions, including cell proliferative index and gene expression, compared with two-dimensional substrates [27,28]. Moreover, similar observations were found between three-dimensional matrices with distinct properties [29].…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, cell culture in a threedimensional spatial arrangement has been reported to affect a range of cellular functions, including cell proliferative index and gene expression, compared with two-dimensional substrates [27,28]. Moreover, similar observations were found between three-dimensional matrices with distinct properties [29].…”
Section: Discussionsupporting
confidence: 66%
“…This investigation found that DC immunity in NPC patients was augmented by FSTL1. Similarly, TNF‐α has been shown to promote the development of immature DCs into mature DCs . Therefore, the mechanism by which FSTL1 expedites the immune ability of DCs should be elucidated from this perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, TNF-α has been shown to promote the development of immature DCs into mature DCs. 54,55 Therefore, the mechanism by which FSTL1 expedites the immune ability of DCs should be elucidated from this perspective. Above all, it is important to investigate the mechanism by which FSTL1 affects DCs to provide a basis for new antitumor immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…[69] The addition of collagen to chitosan increases pores diameter and porosity of the scaffold. [71] [71] …”
Section: Tissue Engineeringmentioning
confidence: 99%